Progressive Systemic Sclerosis With CREST Syndrome. Case Report (Revista de Medicina Clinica, 2023)
Introduction: Progressive systemic sclerosis is a chronic autoimmune disease of unknown cause that attacks connective tissue, and is characterized by vascular alterations and fibrosis of tissues and organs. There is a limited form called CREST, characterized by the presence of calcinosis, Raynaud's phenomenon, esophageal fibrosis, sclerodactyly, and telangiectasias, present in this clinical case. Case Report: 54-year-old female patient with a history of scleroderma diagnosed 5 years ago with multiple amputations, presents for odynophagia, heartburn, burning epigastric pain, Raynaud's phenomenon, calcinosis, also with an ulcerative lesion in the left foot with necrotic appearance, accompanied by pain and also generalized paleness and fatigue. At the time of admission, she was started with antibiotic therapy due to soft tissue infection, two blood packets were transfused due to severe anemia criteria, she also presented esophageal stenosis for which she was dilated with a balloon. Prednisone, Pentoxifylline, Nifedipine, Sildenafil, Methotrexate are added, Calcipatril plus Betamethasone is added. Subsequently, vascular surgery goes to the evaluation of the patient and determines that it requires amputation of the affected limb, however, the patient refused to accept the therapy issued by vascular surgery, and in turn, remains being treated under outpatient consultation while waiting for therapeutic decision. Conclusions: This case is presented because it is a pathology classified as rare, and that due to its complications it is important to share it with the medical community.
Keywords: Systemic Scleroderma; CREST syndrome; Raynaud's disease